Phenotypic heterogeneity of genomically-diverse isolates of Streptococcus mutans. - Sara R Palmer; James H Miller; Jacqueline Abranches; Lin Zeng; Tristan Lefebure; Vincent P Richards; José A Lemos; Michael J Stanhope; Robert A Burne (PLoS ONE, 2013)
High coverage, whole genome shotgun (WGS) sequencing of 57 geographically- and genetically-diverse isolates of Streptococcus mutans from individuals of known dental caries status was recently completed. Of the 57 sequenced strains, fifteen isolates, were selected based primarily on differences in gene content and phenotypic characteristics known to affect virulence and compared with the reference strain UA159. A high degree of variability in these properties was observed between strains, with a broad spectrum of sensitivities to low pH, oxidative stress (air and paraquat) and exposure to competence stimulating peptide (CSP). Significant differences in autolytic behavior and in biofilm development in glucose or sucrose were also observed. Natural genetic competence varied among isolates, and this was correlated to the presence or absence of competence genes, comCDE and comX, and to bacteriocins. In general strains that lacked the ability to become competent possessed fewer genes for bacteriocins and immunity proteins or contained polymorphic variants of these genes. WGS sequence analysis of the pan-genome revealed, for the first time, components of a Type VII secretion system in several S. mutans strains, as well as two putative ORFs that encode possible collagen binding proteins located upstream of the cnm gene, which is associated with host cell invasiveness. The virulence of these particular strains was assessed in a wax-worm model. This is the first study to combine a comprehensive analysis of key virulence-related phenotypes with extensive genomic analysis of a pathogen that evolved closely with humans. Our analysis highlights the phenotypic diversity of S. mutans isolates and indicates that the species has evolved a variety of adaptive strategies to persist in the human oral cavity and, when conditions are favorable, to initiate disease.